2000
DOI: 10.1024/0301-1526.29.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Veränderungen der extrazellulären Matrix in der Venenwand – Ursache der primären Varikosis?

Abstract: If the findings of the present investigation can be confirmed by other studies, alterations in the vein wall may be regarded as the primary cause of varicosis and valvular insufficiency as the result of these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Several experimental and clinical studies suggest that defects in the venous wall may be regarded as the primary cause of varicosis leading to secondary valvular incompetence [4, 5]. Modifications in the media layer of the venous wall appear as general features of varicose veins.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and clinical studies suggest that defects in the venous wall may be regarded as the primary cause of varicosis leading to secondary valvular incompetence [4, 5]. Modifications in the media layer of the venous wall appear as general features of varicose veins.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that an abnormal remodeling occurs in varicose veins [1,2,3] and these alterations of the venous wall may be regarded as the primary cause of varicosis [4, 5]. Dilatations occur because the venous wall is weakened and valvular incompetence is secondary rather than primary [4].…”
Section: Introductionmentioning
confidence: 99%
“…52 Also, biochemical abnormalities similar to those observed in varicose veins have been demonstrated in normal-appearing human saphenous vein wall adjacent to varicose veins and between competent venous valves. 55, 56 We have also shown that prolonged increases in vein wall tension in rat IVC is associated with venous dysfunction and decreased vein contraction. 27 The increased vein wall tension causes an increase in matrix metalloproteinases MMP-2 and MMP-9, and MMPs in turn cause vein wall hyperpolarization and venous relaxation possibly by activating large conductance Ca 2+ dependent K + channels.…”
Section: Discussionmentioning
confidence: 79%